2016
DOI: 10.1007/s00335-016-9664-5
|View full text |Cite
|
Sign up to set email alerts
|

Viable Ednra Y129F mice feature human mandibulofacial dysostosis with alopecia (MFDA) syndrome due to the homologue mutation

Abstract: Animal models resembling human mutations are valuable tools to research the features of complex human craniofacial syndromes. This is the first report on a viable dominant mouse model carrying a non-synonymous sequence variation within the endothelin receptor type A gene (Ednra c.386A>T, p.Tyr129Phe) derived by an ENU mutagenesis program. The identical amino acid substitution was reported recently as disease causing in three individuals with the mandibulofacial dysostosis with alopecia (MFDA, OMIM 616367) synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…On the other hand, the Endothelin receptor B is found in the brain, endothelium, and smooth muscle cells and mediates endothelium‐dependent vasodilation through the release of nitric oxide, prostacyclin, and adrenomedullin (a circulating vasodilatory and natriuretic peptide of vascular endothelial and smooth muscle cell origin) (Issa et al, ; Kawasaki‐Nishihara, Nishihara, Nakamura, & Yamamoto, ). Regarding the role of the Endothelin Receptors in development, it has been shown that the Edn1/Ednra cell signaling plays a critical role in the specification, migration and patterning of mandibular identity in post‐migratory NCCs in different animal models such as Xenopus , zebrafish, chick, rat, rabbit and mouse (Bonano et al, ; Clouthier et al, ; Gordon et al, ; Kempf, Linares, Corvol, & Gasc, ; Miller, Schilling, Lee, Parker, & Kimmel, ; Sabrautzki et al, ; Spence, Anderson, Cukierski, & Patrick, ; Treinen, Louden, Dennis, & Wier, ).…”
Section: Chemical Agentsmentioning
confidence: 99%
“…On the other hand, the Endothelin receptor B is found in the brain, endothelium, and smooth muscle cells and mediates endothelium‐dependent vasodilation through the release of nitric oxide, prostacyclin, and adrenomedullin (a circulating vasodilatory and natriuretic peptide of vascular endothelial and smooth muscle cell origin) (Issa et al, ; Kawasaki‐Nishihara, Nishihara, Nakamura, & Yamamoto, ). Regarding the role of the Endothelin Receptors in development, it has been shown that the Edn1/Ednra cell signaling plays a critical role in the specification, migration and patterning of mandibular identity in post‐migratory NCCs in different animal models such as Xenopus , zebrafish, chick, rat, rabbit and mouse (Bonano et al, ; Clouthier et al, ; Gordon et al, ; Kempf, Linares, Corvol, & Gasc, ; Miller, Schilling, Lee, Parker, & Kimmel, ; Sabrautzki et al, ; Spence, Anderson, Cukierski, & Patrick, ; Treinen, Louden, Dennis, & Wier, ).…”
Section: Chemical Agentsmentioning
confidence: 99%